Penglibatan Wanita Islam dalam Seni - Ali, Fatimah (Jurnal Usuluddin, 1999)
The scope of culture are very wide which involves various forms of arts, music, songs, acting and so on. Islam does not reject any kind of cultures activities if it is done within the boundaries that is allowed by the Syara. This article attempts to discusses Muslim womens participation in culture, in order that they do not over indulge or do anything that is prohibited by Islam.